How Big Does A Prairie Need To Be? - Brian Obermeyer (Symphony in the Flint Hills, 2016)
The Nature Conservancy ecologist Chris Helzer asked how big a prairie needs to be in order to maintain ecological functions or, on the flip side, how much habitat fragmentation—breaking up of landscapes into smaller, unconnected, and dissimilar patches—undermines a prairie.
Keywords: prairie; landscapes; tallgrass; ecosystem; fires; lightning; chicken; habitat; wildlife; European honeybee; BOX CAR; Phil Epp